Errors made by tenth graders at Thuan Thanh II High School in their writing in English = Những lỗi học sinh lớp 10 trường THPT Thuận Thành 2 gặp phải khi học viết bằng tiếng Anh. M.A Thesis Linguistics: 60 14 10 - Đỗ, Văn Lập (University of Languages and International Studies, 2017)
45 p. + CD-ROM